Genetic Analyses of the rbcL and psaA Genes From Single Cells Demonstrate a Rhodophyte Origin of the Prey in the Toxic Benthic Dinoflagellate Ostreopsis - Lee, Bora; Park, Myung G. (Frontiers in Marine Science, 2018)
Phagotrophy of the harmful benthic dinoflagellates of the genus Ostreopsis has long been inferred based on observations of food particles present inside the cell, but the prey was not identified yet. This study aimed to investigate seasonal dynamics of the benthic dinoflagellates Ostreopsis spp.in temperate Korean coastal sites, with special emphasis on their phagotrophy. To further identify the prey, the ingested food particles were extracted from single Ostreopsis cells and their rbcL and psaA genes sequences were determined. High concentration of Ostreopsis cells was observed between June and October at all sites, when water temperatures were higher than 19oC, exhibiting a marked temporal seasonality. The percentage of Ostreopsis cells containing the ingested food particles exhibited the large spatial and temporal variations among sampling sites, ranging from undetectable level to 29.5%, and was not always associated with Ostreopsis cell abundance. Phylogenetic analyses using both plastid-encoded rbcL and psaA genes revealed that all sequences obtained from the ingested food particles of Ostreopsis cells grouped within the class Florideophyceae, Rhodophyta. Our result clearly demonstrates that Ostreopsis species consume various macroalgae from the rhodophyta, not protists which have long been thought to be potential prey. The result from this study provides a basis for better understanding mixotrophic behavior and nutritional ecology of the benthic harmful dinoflagellate Ostreopsis species.